PERBEDAAN PENERAPAN ACCELERATION FACTOR TERHADAP KARAKTERISTIK CITRA DIAGNOSTIK T2WI FSE PADA MRI LUMBAL KASUSHERNIATED NUCLEUS PULPOSUS (HNP) - Maulidya Nasokha Ildsa; Gatot Murti Wibowo; Emi Murniati (Poltekkes Kemenkes Semarang, 2019)
Background: Patients with HNP cases have a bigger chance to do a movement during MRI examination, and it causes poor MRI image. Quick time of MRI examination is needed to produce an optimal image. The technique of parallel imaging is a technique that can increase the speed of MRI data acquisition by passing through several lines of phase encoding in k-space. The GRAPPA technique is one of the methods used to reconstruct data on MRI parallel imaging techniques with better overall image quality. The technique of parallel imaging has a special parameter called acceleration factor. Acceleration factor (R-factor) will affect scan time. The purpose of this research is to know the difference of diagnostic image characteristic which is resulted in applying acceleration factor 2, 3 and 4 in parallel imaging of GRAPPA method and know the optimal acceleration factor to obtain MRI image of lumbar HNP case.Methods: This research type is quantitative research with descriptive approach. The study was conducted by MRI Siemens 3 T in RSUD Dr. Soedono Madiun. The data were 30 MRI images of lumbar sagittal of HNP cases on T2WI FSE with acceleration factor 2, 3 and 4 GRAPPA methodsResult: The results of this study indicate that there are differences in diagnostic image characteristics in the application of acceleration factor 2 and 4, 3 and 4 with VGA test. Acceleration factor value optimal with VGC test known is acceleration factor 2 and 3Conclusion: Based on the result there were differencediagnostic image characteristics of MRI Lumbar in sagital plane Fast Spin Echo (FSE)sequence with variation acceleration factor 2, 3 and 4 parallel imaging GRAPPA methode in case Herniated Nucleus Pulposus (HN0). The optimal value of variation acceleration factor value for MRI Lumbar examination of Heniated Nucleus Pulposus (HNP) is 2 dan 3.